Temporal and structural genetic variation in reindeer (Rangifer tarandus) associated with the pastoral transition in Northwestern Siberia - Røed, Knut; Kvie, Kjersti; Losey, Robert J.; Kosintsev, Pavel A; Hufthammer, Anne Karin; Dwyer, Mark J.; Goncharov, Vasiliy; Klokov, Konstantin B; Arzyutov, Dmitry V.; Plekhanov, Andrei; Anderson, David G. (Ecology and Evolution, 2021)
publishedVersion